A 'catch-and-release' receptor for the cholera toxin. (17th July 2019) - Mahon, Clare S.; Wildsmith, Gemma C.; Haksar, Diksha; de Poel, Eyleen; Beekman, Jeffrey M.; Pieters, Roland J.; Webb, Michael E.; Turnbull, W. Bruce
Abstract : Thermoresponsive receptors for the recognition unit of the cholera toxin (CTB) can recognise the protein with nanomolar affinity. An increase in temperature can drastically reduce their avidity, enabling on-demand release of CTB. Abstract : Stimuli-responsive receptors for the recognition unit of the cholera toxin (CTB) have been prepared by attaching multiple copies of its natural carbohydrate ligand, the GM1 oligosaccharide, to a thermoresponsive polymer scaffold. Below their lower critical solution temperature (LCST), polymers complex CTB with nanomolar affinity. When heated above their LCST, polymers undergo a reversible coil to globule transition which renders a proportion of the carbohydrate recognition motifs inaccessible to CTB. This thermally-modulated decrease in the avidity of the material for the protein has been used to reversibly capture CTB from solution, enabling its convenient isolation from a complex mixture.